2012
DOI: 10.1007/s00256-012-1438-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new low-dose biplanar system to assess lower-limb alignment in 3D: a phantom study

Abstract: The 3D modeling allows for a more accurate evaluation of coronal alignment compared to 2D, eliminating bias due to wrong knee positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
1
41
0
2
Order By: Relevance
“…The KA2 system is similar to conventional extramedullary guides and is therefore simple to learn, with orthopedic surgeons showing substantial reduction in procedure time after experience with just four cadavers [26]. Third, slight variations in limb position during acquisition of radiographs can affect alignment measurements [40]. Computed tomography can measure alignment controlling for variations in limb position.…”
Section: Discussionmentioning
confidence: 99%
“…The KA2 system is similar to conventional extramedullary guides and is therefore simple to learn, with orthopedic surgeons showing substantial reduction in procedure time after experience with just four cadavers [26]. Third, slight variations in limb position during acquisition of radiographs can affect alignment measurements [40]. Computed tomography can measure alignment controlling for variations in limb position.…”
Section: Discussionmentioning
confidence: 99%
“…Guenoun et al [19] found similar low mean interreader differences for assessment of limb length (0.2 cm) and mechanical axis (0.5°) measured on 2D BPR images. Interestingly, both Guenoun et al [19] and Thelen et al [20] found, that the assessment of lower limb length is more accurate with measurements based on 3D-BPR than on coronal 2D-BPR due to a better elimination of wrong knee positioning. Since Thelen et al [20] only found relevant errors in knee flexion more than 10 degrees and since coronal 2D-measurements are much more established and easier to perform, we chose the 2D measurements for comparison of micro-dose and low-dose BPR images.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, both Guenoun et al [19] and Thelen et al [20] found, that the assessment of lower limb length is more accurate with measurements based on 3D-BPR than on coronal 2D-BPR due to a better elimination of wrong knee positioning. Since Thelen et al [20] only found relevant errors in knee flexion more than 10 degrees and since coronal 2D-measurements are much more established and easier to perform, we chose the 2D measurements for comparison of micro-dose and low-dose BPR images. Recent studies have already shown that femoral and tibial torsion measurements based on 3D low-dose BPR are reliable [19] and comparable to CT measurements in children, adolescents, and adults [10,11,21].…”
Section: Discussionmentioning
confidence: 97%
“…When a measurement is taken in 3D, the system mathematically corrects for potential malpositioning during acquisition. EOS VV3D measurements of legs that not contain a knee prosthesis are more accurate than VV2D measurements, eliminating bias due to wrong lower-limb positioning [31]. Validity of EOS VV3D on legs not containing prosthetic material was also investigated in a cadaveric study [19] that measured varus/valgus angle three times using CT-scanning and EOS 3D with each specimen in three different positions: neutral, 10° external rotation and 10° internal rotation.…”
Section: Discussionmentioning
confidence: 99%